2014
DOI: 10.1016/j.jpsychires.2014.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and perinatal risk factors in a twin study of autism spectrum disorders

Abstract: Introduction Multiple studies associate prenatal and perinatal complications with increased risks for autism spectrum disorders (ASDs). The objectives of this study were to utilize a twin study design to 1) Investigate whether shared gestational and perinatal factors increase concordance for ASDs in twins, 2) Determine whether individual neonatal factors are associated with the presence of ASDs in twins, and 3) Explore whether associated factors may influence males and females differently. Methods Data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 47 publications
6
46
0
2
Order By: Relevance
“…While disaggregating perinatal complications from ASD is challenging because susceptibility might have led to perinatal complications and ASD, they point to two hypotheses:

Hypoxia: Obstetrical complications related to hypoxia pose significant risk in meta-analyses (90). This is supported by a recent twin study indicating that respiratory distress and other markers of hypoxia increased ASD risk (91). Relationships between brain hypoxia and social behavior deficits warrant further attention.

Immunologic: Studies link maternal infections during pregnancy to ASD in offspring (89, 90).

…”
Section: Genetic Epidemiology In Asdsupporting
confidence: 64%
See 1 more Smart Citation
“…While disaggregating perinatal complications from ASD is challenging because susceptibility might have led to perinatal complications and ASD, they point to two hypotheses:

Hypoxia: Obstetrical complications related to hypoxia pose significant risk in meta-analyses (90). This is supported by a recent twin study indicating that respiratory distress and other markers of hypoxia increased ASD risk (91). Relationships between brain hypoxia and social behavior deficits warrant further attention.

Immunologic: Studies link maternal infections during pregnancy to ASD in offspring (89, 90).

…”
Section: Genetic Epidemiology In Asdsupporting
confidence: 64%
“…This is supported by a recent twin study indicating that respiratory distress and other markers of hypoxia increased ASD risk (91). Relationships between brain hypoxia and social behavior deficits warrant further attention.…”
Section: Genetic Epidemiology In Asdsupporting
confidence: 64%
“…Few studies have examined whether offspring sex is a factor for exposures and autism risk. A study of 194 twins found that respiratory distress and hypoxia increased the risk of ASD in males, while jaundice was associated with its increased risk in female offspring [76]. They hypothesized that males may be more prone to hypoxic brain injury (HI) than females as testosterone can potentiate HI and progesterone and allopregnanolone can be protective in animal models.…”
Section: Prenatal Programming Of Neuropsychiatric Disordersmentioning
confidence: 99%
“…One explanation is that autistic miRNA patterns may represent a permanent response to an early environmental insult, such as perinatal hypoxia (61). In this scenario, miRNA regulation could be disrupted by a layer of epigenetic machinery such as DNA methylation.…”
Section: Introductionmentioning
confidence: 99%